Evolution of Rift Architecture and Fault Linkage During Continental Rifting: Investigating the Effects of Tectonics and Surface Processes Using Lithosphere‐Scale 3D Coupled Numerical Models. Issue 12 (13th December 2022) - Wolf, Lorenz; Huismans, Ritske S.; Wolf, Sebastian G.; Rouby, Delphine; May, Dave A.
Abstract: Continental rifts grow by propagation, overlap and linkage of individual fault segments. These processes are influenced by erosion and sedimentation and generate complex three‐dimensional fault‐interaction patterns. We use a 3D thermo‐mechanical model of lithosphere deformation coupled with surface processes to investigate the coupling between erosion and tectonics, fault interaction and rift linkage, and evaluate the respective characteristics of crustal strength, inherited structures and erosional efficiency. We find that (a) weaker crust limits interactions between individual rift segments, (b) inherited structures are a major control for fault overlap and linkage except if they are too far apart and prevent interaction, and (c) efficient surface processes prolong fault activity, increase accommodated offset and in doing so, limit fault segment propagation and interactions. From these individual feedbacks, we identify five types of characteristic rift architectures: (a) for strong crust and intermediate erosional efficiency, fault segments link and form a horst between the propagating rifts. (b) Decreasing notch offset leads to segmentation of the central horst. (c) In case of reduced crustal strength no fault linkage occurs and a continuous central horst is promoted. (d) If inherited structures are too far apart, irrespective of crustal strength and erosional efficiency, rift basins do not link and a wide plateau‐like horst forms between the propagating rifts. (e) In case of efficient erosion, fault linkage is achieved by the formation of strike‐slip faults connecting the individual rift segments. Several of these simulated rift architectures can be identified in the western branch of the East African Rift. Plain Language Summary: Continental rifting occurs as a response to extensional, tectonic forces. As a consequence, rifts extending over tens to hundreds of kilometers and consisting of subsided basins and high‐elevation rift shoulders are formed at the surface of the Earth. These rifts consist of individual rift segments that interact with each other during the million‐year long evolution of the rifts, resulting in a complex rift architecture. What impacts rift segment interaction is widely disputed, and here we use a 3D computer model to investigate the evolving rift architecture between two rift segments. We see that the mechanical strength of the Earth's crust, preexisting structures and the efficiency of erosion at the surface of the Earth have a strong impact on rift segment interaction. Depending on the feedback between these three factors, we observe five characteristic patterns of rift architecture showing variable degrees of interaction and linkage between the individual rift segments. As a particular case, we observe rift linkage through the formation of strike‐slip faults for very efficient erosion in our simulations. Moving from simulations to natural examples of rifting, several of our simulated architectures can be identified in the western branch of the East African Rift System. Key Points: 3D coupled thermo‐mechanical‐landscape evolution models show development of offset continental rift basins Models show five styles of rift linkage depending on rift offset, crustal rheology, and surface process efficiency The 3D models explain characteristic features of offset rift basins observed in the East African Rift system